Compensation for personal injury in English, German and Italian law : a comparative outline - Markesinis, Basil, 1944- (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2005)
Cross-border claims for personal injuries are becoming more common. Furthermore, European nationals increasingly join class actions in the USA. These tendencies have created a need to know more about the law of damages in Europe and America. Despite the growing importance of this subject, there is a dearth of material available to practitioners to assist them in advising their clients as to the heads of damage recoverable in other countries. This book aims to fill that gap by looking at the law in England, Germany and Italy. The book's introduction sets out the raw data in the wider context of tort law. The final chapter provides a closer synthesis, largely concerned with methodological issues, and draws some comparative conclusions.